2017
DOI: 10.1111/bjhp.12239
|View full text |Cite
|
Sign up to set email alerts
|

What impact do questionnaire length and monetary incentives have on mailed health psychology survey response?

Abstract: ObjectivesResponse rates to health‐related surveys are declining. This study tested two strategies to improve the response rate to a health psychology survey mailed through English general practices: (1) sending a shortened questionnaire and (2) offering a monetary incentive to return a completed questionnaire.DesignRandomized controlled trial.MethodsAdults (n = 4,241) aged 45–59 years, from four General Practices in South‐East England, were mailed a survey on attitudes towards bowel cancer screening. Using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
2
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 58 publications
3
26
2
5
Order By: Relevance
“…The proportion of missing data was small. However, the study has limitations: (i) Although our response rate was reasonable for an unincentivized postal survey, and compares to the response rate of other postal surveys in the UK [41,42] and that of previous a previous European transplant survey [43], there is a risk of self-selection bias. We have reported in our results that our population appeared population representative (Table S2).…”
Section: Discussionmentioning
confidence: 80%
“…The proportion of missing data was small. However, the study has limitations: (i) Although our response rate was reasonable for an unincentivized postal survey, and compares to the response rate of other postal surveys in the UK [41,42] and that of previous a previous European transplant survey [43], there is a risk of self-selection bias. We have reported in our results that our population appeared population representative (Table S2).…”
Section: Discussionmentioning
confidence: 80%
“…The generalizability of the present study is further limited by biases that may have been introduced by our sampling method: sending out email invitations, advertising our study in person at local support groups (this accrued the smallest return), and advertising it on social media. A number of studies have documented that women are generally more likely than men to engage with online surveys [82][83][84], and our disproportionate ratio of females to males would seem consistent with this observation, despite its incongruence with the elevated ratio of males to females diagnosed with autism [85,86]. Notably, studies concerning mental health in non-autistic people have linked the lower up-take by men to the greater stigma that men experience around discussing and seeking help for mental ill-health [87][88][89][90][91][92].…”
Section: Limitations and Directions For Future Studymentioning
confidence: 99%
“…The relationship between monetary incentive and response to mailed questionnaires may be influenced by the value of the incentive and mediated by participant characteristics . For example, UK participants living in more affluent areas were significantly more likely than those in areas of greater deprivation to respond to a mailed health behaviour questionnaire with a conditional £5 incentive but not with a conditional £2.50 incentive . It is therefore useful to explore whether groups from areas of greater deprivation respond differently to those in affluent areas to more proactive recruitment and data collection methods such as the offer of unconditional monetary incentives.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals from the most deprived socio‐economic groups can be more difficult to engage in mailed questionnaire research even when monetary incentives are offered. A UK study found a statistically significantly lower response rate in the most deprived quartile (39%) compared with the least deprived quartile (52%) …”
Section: Introductionmentioning
confidence: 97%